Implementasi Nilai-nilai Pendidikan Karakter di Pondok Pesantren Modern Al-Syaikh Abdul Wahid Kota Baubau Sulawesi Tenggara - Safaruddin Yahya (Jurnal Akademik FKIP Unidayan, 2020)
Character education is a conscious effort to instill and shape good values in individuals or society through the habit to form good personality and good character. Islamic boarding schools in this case are educational institutions whose role is undoubtedly inshaping the character and character of the nation. This study aims to determine how the implementation of character education values in Islamic boarding school Al-Shaykh abdul wahid, what character values are implanted and how the impac to finstilling the secharacter values on students. This study uses qualitative methods, a type of case study with a single case design. Qualitative research was chosen to describe and analyze phenomena, events, learning activities at the research location. The research findings show: (1) Implementation of character education in Islamic boarding schools Al-Shaykh Abdul Wahid is carried out through three stages of activities, namely: through teaching and learning activities (KBM), extra curricular activities, and religious activities of students carried out in the formof programs daily, weekly, monthly, and yearly, (2) Character values that are instilled in Islamic boarding school Al-Shaykh Abdul Wahid's are: religious character, independent character, discipline character and social care character implemented in santri life., (2) The implications of character education in islamic boarding school Al-Shaykh abdul wahid indicate an increase in santri awareness in obeying the rules of the cottage as well as growing independence and responsibility in completing the tasksgiven.